نفسیاتی جنگ کی بابت نبوی حکمت عملی؛ تحقیقی مطالعہ: Prophetic Strategies for Psychological Warfare; Research study - Dr. Hafiz Rizwan Abdullah; Dr. Hafiz Muhammad Arshad Iqbal (MEI, 2023)
Psychological warfare refers to a set of actions and operations that can be used to weaken the enemy or to prevent adversarial psychological action without engaging in combat. In Islamic law, it is considered jihad for the sake of Allah. Psychological warfare is very important for lowering the morale of the enemy and breaking their courage. The Prophet (peace be upon him) used the psychological warfare against his enemy to deal with the major problems that he faced in his life, especially after the formation of the state of Medina.In view of the dangers of psychological warfare and its effects on Islamic society, the Prophet (peace be upon him) took precautionary measures to deal with this war and reduce its effects. The Prophet's strategy in psychological confrontation consisted of strong and disciplined rules that guaranteed the peace and security of society, so the heads of Islamic countries should adopt this strategy and tactics of the Prophet because the responsibility of the Ummah and the Islamic State rests on their shoulders.As well as the intellectual conflict and media aggression, that our society is facing, especially the intellectual aggression that our youth are facing, in this situation we would make this proposal to the leaders of academic, invitational, educational and media institutions. They should include in their curriculum and programs the steps and tactics of the Prophetic strategy to deal with this intellectual and psychological warfare because there is nothing more effective than his strategy and tactics to win the war. This research article presents a research study of the same prophetic strategy.